ASPECTS OF DIFFICULTY OF CONDITIONAL SENTENCES IN BUSINESS NEGOTIATION - Frinadiniarta Nur (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2017)
For speakers of English as a second language, language barriers cause problems in reaching successful negotiation. One of the most difficult sentence construction to comprehend is conditional sentences. The conditional sentence is a complex sentence that consists of a main clause and a subordinate clause; the latter typically begins with the adverbial subordinator if. Some grammarians divide conditional sentences into three structures: Future conditional, Present conditional, and Past conditional. These three structures are also known as type 1, type 2, and type 3 conditional sentences respectively. An experiment was conducted to find out which aspects of conditional sentences cause problems and which do not cause problems for Indonesian learners of English. This experiment employed three kinds of tests: comprehension, production, and discourse testing, in order to analyze two skills: receptive and productive skill. Five aspects were analyzed to find out which one(s) Indonesian learners of English tend to struggle with. The first aspect was the conditional types: type 1, type 2, and type 3. The result showed that there was no fixed hierarchical order of difficulty among conditional sentences under investigation. Moreover, the result showed that the learners did not have any problem comprehending all the three types, but they had problems in producing grammatically correct conditional sentences. The second aspect analyzed was the positive and negative conditional sentences. The analysis showed that the negative conditional sentences caused significantly more problems to the learners (i.e. affected both their receptive and productive skill) than the positive ones. The third aspect under investigation was the involvement of the first and/or the second person. The result showed that the presence of the first and/or the second person in the conditional sentences could significantly promote learners’ receptive and productive skill. The fourth aspect was the position of the if clause, be it in the initial or the final position. The result showed that the position of the if clause did not significantly affect learners’ receptive and productive skill. The last aspect under study was the location of the information, be it in the main clause or in the if clause. The result showed that the conditional sentence was significantly easier to comprehend when information was located in the main clause than when it was in the if clause.